MAX-Phase Films Overcome Scaling Limitations to the Resistivity of Metal Thin Films - Yoo, Joung Eun; Sung, Ju Young; Hwang, Jin Ha; Maeng, Inhee; Oh, Seung Jae; Lee, Inho; Shim, Ji Hoon; Kim, Sung Dug; Yoon, Du Seop; Jang, Seo Young; Kang, Young Jae; Lee, Sang Woon (ACS Applied Materials and Interfaces, 2021)
Metal thin films have been widely used as conductors in semiconductor devices for several decades. However, the resistivity of metal thin films such as Cu and TiN increases substantially (>1000%) as they become thinner (<10 nm) when using high-density integration to improve device performance. In this study, the resistivities of MAX-phase V2AlC films grown on sapphire substrates exhibited a significantly weaker dependence on the film thickness than conventional metal films that resulted in a resistivity increase of only 30%, as the V2AlC film thickness decreased from approximately 45 to 5 nm. The resistivity was almost identical for film thicknesses of 10-50 nm. The small change in the resistivity of V2AlC films with decreasing film thickness originated from the highly ordered crystalline quality and a small electron mean free path (11-13.6 nm). Thus, MAX-phase thin films have great potential for advanced metal technology applications to overcome the current scaling limitations of semiconductor devices.
Keywords: Device performance; Film-thickness; High-density integration; MAX-phase; Metal thin film; Resistivity; Sapphire substrates; Scaling limitation; Sizes effect; Weak dependences; MAX phase; metal thin film; resistivity; scattering; size effect